2019
DOI: 10.1111/jep.13277
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term impact of an interprofessional humanistic faculty development programme: A qualitative investigation

Abstract: Rationale, aims, and objectives: While it has long been supported that faculty development programmes serve as a means to improving practical knowledge, professional skills, and identity formation for faculty, significantly less research is focused on how learning that occurs in faculty development programmes is actually employed in the workplace and ingrained in day-to-day activities. The present study qualitatively explored the long-term impact of the Mentoring and Professionalism in Training (MAP-IT) progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Mentor education is important because there is a growing sentiment in the mentoring literature that to be effective, mentors need specific development activities focused on how to be "humanistic mentors". [89][90][91] Few programs provided evidence to support choices they made regarding career stage of the faculty member or the chosen program structure. Outcome measures were inconsistently captured and often subjective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentor education is important because there is a growing sentiment in the mentoring literature that to be effective, mentors need specific development activities focused on how to be "humanistic mentors". [89][90][91] Few programs provided evidence to support choices they made regarding career stage of the faculty member or the chosen program structure. Outcome measures were inconsistently captured and often subjective.…”
Section: Discussionmentioning
confidence: 99%
“…Mentor education is important because there is a growing sentiment in the mentoring literature that to be effective, mentors need specific development activities focused on how to be “humanistic mentors”. 89–91…”
Section: Discussionmentioning
confidence: 99%
“…Fornari et al 13 showed the MAP-IT program's durable positive influence on self-care and wellness, with subsequent qualitative analyses revealing notable themes of mindfulness, mentorship, professionalism, interprofessional collaboration, and appreciative inquiry. 14 These findings led the authors to hypothesize that the MAP-IT program might serve as a beneficial intervention to enhance resilience and mitigate burnout. This study confirms that inference.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the program curriculum are shown in Table 1. Both participants and leaders were evaluated in each of the prior cohorts 13,14 and this continued with cohort four participants and leaders who, for consistency, completed pre-and post-program assessment instruments.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation